Croatian Galicias : Ideologies of Literary Representations - Vuković, Petar (Array, 2004)
The paper deals with the transformations of the motif of Galicia in the Croatian literatures. It is pointed out that the background of these transformations were always changes in the dominant ideology of the Croatian elites.